PENYULUHAN PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA MTS PONPES DAAR AL-ILMI - Sarah Caesarani; Awanda Eka Syfani; Desti Kartika Sari; Sinta Amelia; Yulia Alfiyana (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2023)
Field Experience Practices (PPL) is one of the compulsory subjects for all students majoring in Information Technology Education at Bina Bangsa University. This field experience practices is intended to train in the application of scientific methods that have been received by Bina Bangsa University students majoring in information technology education. Training as teaching staff in the form of service is held at Mts Ponpes Daar Al Ilmi University of Bina Bangsa for the academic year 2023/2024 is a socialization and training activity to student for information and communication technology subjects. The implementation of the field experience practices program at Mts Ponpes Daar Al Ilmi aims to increase student motivation in information and communication techmology subjects with learning media and implementing practices using available facilities so as to increase significant learning outcomes. The result of this field experience practices : 1) increase students learning motivation and 2) increase students knowledge of information and communication technology. Therefore, the dedication carried out by Bina Bangsa University field experience practice (PPL) student to Mts Ponpes Daar Al Ilmi to students 2023/2024 has been going well